Investigation of PALB2 Mutation and Correlation With Immunotherapy Biomarker in Chinese Non-Small Cell Lung Cancer Patients - Zhang, Jiexia; Tang, Shuangfeng; Zhang, Chunning; Li, Mingyao; Zheng, Yating; Hu, Xue; Huang, Mengli; Cheng, Xiangyang (Frontiers in Oncology, 2022)
Background：PALB2, a gene in the homologous recombination repair (HRR) pathway of the DNA damage response (DDR), is associated with the efficacy of platinum-based chemotherapy, immunotherapy, and PARP inhibitor therapy in several tumors. However, the PALB2 characteristics, its correlation with immunogenic marker, and the predictive value of immunotherapy in non-small cell lung cancer (NSCLC) were unknown. Methods: Tumor tissue samples from Chinese NSCLC were analyzed by next-generation sequencing (NGS) (panel on 381/733-gene). TMB is defined as the total number of somatic non-synonymous mutations in the coding region. MSI was evaluated by NGS of 500 known MSI loci. PD-L1 expression was evaluated using immunohistochemistry (Dako 22C3). Two independents (the OAK and POPLAR study cohort) with data from 429 patients, and one cohort (Rizvi2018.NSCLC.240.NGS cohort) with data from 240 patients with advanced NSCLC, were used to analyze the prognostic effect of PALB2 on immunotherapy. Result: Genetic mutation of 5227 NSCLC patients were analyzed using NGS, of which 162 (3.1%) harboured germline PALB2 mutation (PALB2gmut) and 87 (1.66%) harboured somatic PALB2 mutation (PALB2smut). In NSCLC patients with PALB2gmut and PALB2smut the most frequently mutated genes were TP53 (65%, 64%). PALB2smut (14.52 Muts/Mb) was associated with higher TMB (P < 0.001) than PALB wild-type (PALB2wt) (6.15 Muts/Mb). But there was no significant difference in TMB between PALB2gmut (6.45 Muts/Mb) and PALB2wt (6.15 Muts/Mb) (P=0.64). There was no difference in PD-L1 expression among PALB2gmut, PALB2smut, and PALB2wt. No correlation was found with PD-L1 expression. In Rizvi2018.NSCLC.240.NGS cohort, there was no difference in progression-free survival (PFS) (HR =1.06, P=0.93) between PALB2 mutation (3.15 months) and PALB2wt (3.17 months). The OAK and POPLAR study cohort of NSCLC patients showed that there was no difference in overall survival (OS) (HR =1.1, P=0.75) between PALB2 mutation (10.38 months) and PALB2wt (11.07 months). Conclusions: These findings suggest that PALB2 may not be used as a biomarker for determining prognosis on immunotherapy in NSCLC.